Evaluation of environmental literacy among polytechnic business students : A case study in Politeknik Sultan Salahuddin Abdul Aziz Shah - Ramdas, Murugadas; Mohamed, Badaruddin (2013)
This study is conducted to evaluate the environmental literacy of polytechnic business students when it was found that their employability was lower than students from to other fields. This due to the fact that there are sufficient employment opportunities for business students in the environmental field. A total number of 269 questionnaire were distributed to business student from Politeknik Sultan Salahuddin Abdul Shah stratified according to according gender and business programs. Analysis results show that level of environmental literacy was at a very low level. A significant relationship between environmental literacy and environmental activity was also found. Male students tend to have higher level of environmental literacy than female students where else students from International Business had higher level of environmental literacy than other programs.